A novel image encryption scheme based on DCT transform and DNA sequence - Ali A. Yassin; Abdullah Mohammed Rashid; Abdulla J. Yassin; Hamid Alasadi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Recently, the concept of DNA has been invested in computing technology in different ways which linking information technology and biological sciences. There are several encryption algorithms based on DNA encoding that has been proposed, which leads to generating a new direction in image encryption. However, the DNA encryption scheme has drawbacks such as expensive experimental equipment, difficult operations, and hard to hold its biotechnology. Additionally, during careful cryptanalysis that applied to most of these image encryption schemes, we notice that DNA operators can only influence one DNA base, which causes poor diffusion. Our proposed scheme is not applied complex biological operation but just is given to improve the diffusion ability of image encryption scheme by using DNA sequence and DCT transform. Our works overcome above-aforementioned issues. Furthermore, empirical results on real images and security analysis demonstrate that our proposed scheme not only has flexibility and efficiency encryption scheme but also has the ability to resist well-known attacks such as entropy attack, differential attack, statistical attack, chosen/known plain image attack. Additionally, our work enjoys several strong characteristics as follows: (1) the decryption error is very low to recover the original image; (2) Once key for each encryption process and if the user wants to use the same key in many times, our proposed scheme supports secret key sensitivity; (3) the value of correlation of the encrypted image is null; (4) the scrambling process is good and generate high disorder at the output. As a result, our proposed scheme achieves a good balance between strong security and high performance.